ANALISIS TERJEMAHAN EUFEMISME ORGAN DAN AKTIFITAS SEKSUAL DALAM NOVEL FIFTY SHADES OF GREY - Arifin, Desi Zauhana; Djatmika, Djatmika; Wiratno, Tri (Universitas Sebelas Maret, 2017)
This research is aimed to: (1) identify the kinds of euphemism sexual organ and sexual activity in Fifty Shades of Grey novel, (2) identify the translation techniques used by the translator in translating sexual organ and sexual activity with euphemism, (3) describe the impact of translation technique which applied by the translator toward translation quality in terms of accuracy and acceptability.This research is a descriptive-qualitative research. Sources of data are Fifty Shades of Grey novel and also informans who assess the quality of the translation. Data were collected by using document analysis, questionnaires, and focus group discussion (FGD). Data were analyzed by using Spradley’s ethnography method.The result of this research shows that there are 10 kinds of euphemism in sexual organ and sexual activity in Fifty Shades of Grey novel . The most dominating euphemism sexual organ of this data is general for specific with the percentation as many as 47.14%, while in sexual activity, the most dominating euphemism is hyperbole with percentation 29.37%. In this research there are thirteen techniques which used by the translator to translate sexual organ and sexual activity with euphemism, the technique which dominates is established equivalent with the percentation 47.43%. For the translation quality, 117 data (59,7%) were accurately translated, 66 data (33,7%) were less accurately translated 13 data (6,6%)were not accurately translated and there were 112 data (57,1%) identified as acceptable translation, 74 data (37,8%) are less acceptable translation, and 10 data (5,1%) are not acceptable translation.The conclusion of this research shows that lots of euphemisms were found in Fifty Shades of Grey novel and some of translation techniques have negative impact towards the translation quality of Fifty Shades of Grey novel. This research only uses euphemism sexual organ and sexual activity in Fifty Shades of Grey novel. The other reference of euphemism can be used as the data for further research. Keywords: Euphemism, translation techniques, translation quality